2015
DOI: 10.1002/oby.21194
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity in persons with chronic spinal cord injury determined by dual energy X‐Ray absorptiometry

Abstract: Objective: To determine visceral adipose tissue (VAT) volume (VAT vol ) by dual energy X-ray absorptiometry (DXA) in spinal cord injured (SCI) and able-bodied (AB) participants and to explore the relationships between VAT vol and routine anthropometric measures. Methods: Sixty-three subjects with SCI and 126 healthy male AB controls were stratified as low risk [LR: waist circumference (WC) < 102 cm] and moderate to high risk (MHR: WC 102 cm) for identification of risk for cardiometabolic disease: AB-LR, SCI-LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Those with higher cord lesions are also generally less active, which may predispose to abdominal obesity as well. SAT volume, as expected, was similar among all groups [46], as was AF volume, but VAT volume in each of the SCI groups was similar and about two-fold higher than that observed in the AB group, confirming previous work related to visceral adiposity in those with SCI despite similar body mass index values to able-bodied cohorts [30]. Accumulation of VAT is strongly associated with the metabolic syndrome, type 2 diabetes mellitus, and heightened risk of cardiovascular disease [47,48], and visceral adiposity is positively associated with insulin resistance [49].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Those with higher cord lesions are also generally less active, which may predispose to abdominal obesity as well. SAT volume, as expected, was similar among all groups [46], as was AF volume, but VAT volume in each of the SCI groups was similar and about two-fold higher than that observed in the AB group, confirming previous work related to visceral adiposity in those with SCI despite similar body mass index values to able-bodied cohorts [30]. Accumulation of VAT is strongly associated with the metabolic syndrome, type 2 diabetes mellitus, and heightened risk of cardiovascular disease [47,48], and visceral adiposity is positively associated with insulin resistance [49].…”
Section: Discussionsupporting
confidence: 83%
“…Proprietary software algorithms from the manufacturer were used to analyze the scans and compute total body fat mass and standard regions of interest (ROI) for each participant. From a DXA total body image, subcutaneous adipose tissue (SAT) mass and VAT mass were obtained from the abdominal android fat (AF) mass region by using iDXA enCoreTM CoreScan software package, which is a FDA-approved software upgrade for the iDXA that has been validated against computer tomography (CT; R 2 = 0.957) to measure VAT [29]; a recent report from our group demonstrated the utility of this measure to capture abdominal adiposity in persons with SCI [30]. The abdominal AF mass ROI was defined as the area that begins at the proximal border of the iliac crest and has a height that is 20% of the total distance from the proximal border of the iliac crest to the base of the skull.…”
Section: Methodsmentioning
confidence: 99%
“…Spinal cord injury (SCI) is associated with severe reductions in the health of the musculoskeletal system due to disuse and immobilization below the spinal lesion. The extensive muscle atrophy (Qin, Bauman, & Cardozo, ) that occurs after SCI is associated with reductions in systemic glucose handling and elevated rates for developing type II diabetes mellitus and cardiovascular diseases (Bauman & Spungen, ; Gorgey et al, ), outcomes linked with the accumulation of visceral fat tissue (Cirnigliaro et al, ) and a potential rise in systemic pro‐inflammatory cytokines (Rosen & Spiegelman, ). Skeletal muscle has been recognized to be an endocrine organ (Pedersen & Febbraio, ) and it has also been shown to be associated with markers of inflammation in disease states, which cause muscle atrophy (Londhe & Guttridge, ), although the exact role of skeletal muscle in creating or sustaining this pro‐inflammatory condition compared to infiltration by immune or other cell types, as well as dysfunctional satellite cells, has not been explicitly answered.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with SCI have a 27% increase in VAT for every one-centimeter increase in WC, and a 20% increase in VAT for every one-unit increase in BMI when compared to D r a f t 4 matched able-bodied controls (Cirnigliaro et al, 2015). At any given BMI, individuals with SCI have up to a 43% increased VAT volume when compared to the able-bodied population (Cirnigliaro et al, 2015). Previous studies have indicated that neurological level of injury or injury severity (ASIA Impairment Scale) of SCI are not associated with VAT (Gorgey and Gater, 2011;Pelletier et al, 2016).…”
mentioning
confidence: 97%
“…Both total VAT and the VAT to SAT ratio are consistently reported as higher among adults with SCI when compared to age and sex matched peers in the general population after controlling for waist circumference (WC) and body mass index (BMI) (Edwards et al 2008). Individuals with SCI have a 27% increase in VAT for every one-centimeter increase in WC, and a 20% increase in VAT for every one-unit increase in BMI when compared to D r a f t 4 matched able-bodied controls (Cirnigliaro et al, 2015). At any given BMI, individuals with SCI have up to a 43% increased VAT volume when compared to the able-bodied population (Cirnigliaro et al, 2015).…”
mentioning
confidence: 99%